2022
DOI: 10.1002/mds.28953
|View full text |Cite
|
Sign up to set email alerts
|

Lateralized Subthalamic Stimulation for Axial Dysfunction in Parkinson's Disease: A Randomized Trial

Abstract: Background Patients with Parkinson's disease might develop treatment‐resistant axial dysfunction after bilateral subthalamic stimulation. Objectives To study whether lateralized stimulation (unilateral 50% amplitude reduction) for ≥21 days results in ≥0.13 m/s faster gait velocity in the dopaminergic ON state in these patients, and its effects on motor and axial function, quantitative gait and speech measures, quality of life, and selected cognitive tasks. Methods Randomized, double‐blinded, double‐crossover t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…The published data are however contradictory up to now. In a recent randomized cross-over study, reducing left STN-DBS amplitude by 50% was found to decrease axial motor signs and FOG-Q, but no significant change was found when reducing the right STN-DBS amplitude [36]. In another randomized study, reducing stimulation amplitude by 30% contralateral to the least affected side had no positive effect with conversely an aggravation of symptoms, leading to a premature drop-out for 8/12 patients [37].…”
Section: Discussionmentioning
confidence: 93%
“…The published data are however contradictory up to now. In a recent randomized cross-over study, reducing left STN-DBS amplitude by 50% was found to decrease axial motor signs and FOG-Q, but no significant change was found when reducing the right STN-DBS amplitude [36]. In another randomized study, reducing stimulation amplitude by 30% contralateral to the least affected side had no positive effect with conversely an aggravation of symptoms, leading to a premature drop-out for 8/12 patients [37].…”
Section: Discussionmentioning
confidence: 93%
“… 36 , 37 However, Lizárraga et al . 38 recently proposed that FOG-Q and axial motor signs are greatly associated with the left STN-DBS amplitude other than the right STN-DBS. No difference in post-operative FOG severity after the right and left STN-DBS has also been reported by other studies.…”
Section: Discussionmentioning
confidence: 99%